Business planning and market strategy - Valentin, Erhard K. (SAGE Publications, Inc, 2014)
Business Planning and Market Strategy offers students, entrepreneurs, and executives penetrating insights into developing business plans and market strategies that bolster the odds of succeeding in today's highly competitive marketplace. Rather than reduce the planning process to mechanistic, step-by-step instructions, which promote 'thinking inside the box', author E.K. Valentin provides practical planning guidelines that encourage creative strategic problem solving. Drawing on both his business experience and the business literature, he explains not only what entrepreneurs and executives should look at when pondering plans and strategies, but also what they should look for. The book's unique applied perspective, sets Business Planning & Market Strategy apart from conventional 'how to' planning guides.- Resumé vydavatel